AN EVALUATION OF RIVER SAKI-JIKI STREAM WATER QUALITY IN BATSARI KATSINA STATE NIGERIA - Adamu G. K; Aliyu I. Kankara; Rabi’u Tukur; Ibrahim Abdulrashid (European Scientific Journal, ESJ, 2013)
Environmental hydrogeo-chemistry is unique in focusing directly on the presence of dissolved salts and other contaminants observed in the surface and ground water sources, resulting in intriguing fall in the productivity of public health issues related to environment. This is mostly brought by Intensive human and agricultural activity. Trace elements, normally present in minute quantities in the stream water are a major influence on health. Chemical data itself can be used to obtain information about geological processes. Spectro-photometric methods and procedures for the evaluation of water samples were use to obtain values of concentrations of a selected number of alkaline elements and their compounds, in addition to other water condition indicators. These were sampled and evaluated. The result of the research shows that, all the parameters tested show variations when compared with the control site, but the concentration is not severe to the level it makes the water not suitable for either domestic or agricultural use. The study therefore, recommended for frequent monitoring of the soil, sand, water conditions in order to detect early signs of hazards.